VceC Mediated IRE1 Pathway and Inhibited CHOP-induced Apoptosis to Support Brucella Replication in Goat Trophoblast Cells - Zhi, Feijie (Int J Mol Sci, 2019)
The effectors of the type IV secretion system (T4SS) of bacteria play important roles in mediating bacterial intracellular proliferation and manipulating host-related pathway responses to bacterial infection. Brucella Spp. inhibit the apoptosis of host cells to benefit their own intracellular proliferation. However, the underlying mechanisms between T4SS effectors and Brucella-inhibited apoptosis in goat trophoblast cells remain unclear. Here, based on Brucella suis vaccine strain 2, the VceC was deleted by allelic exchange. We show that ΔVceC was able to infect and proliferate to high titers in goat trophoblast cells (GTCs) and increase C/EBP-homologous protein (CHOP)-mediated apoptosis. GRP78 expression decreased upon ΔVceC infection. In addition, we discovered that the inositolrequiring enzyme 1 (IRE1) pathway was inhibited in this process. Changing endoplasmic reticulum (ER) stress affected Brucella intracellular replication in GTCs. The replication of ΔVceC was more sensitive under the different ERstress conditions in the GTC line after treatment with ER stress inhibitors 4 phenyl butyric acid (4-PBA) or ER stress activator Tm. Together, our findings show that VceC has a protective effect on the intracellular persistence of Brucella infection, and inhibits ER stress-induced apoptosis in the CHOP pathway. The present work provides new insights for understanding the mechanism of VceC in the establishment of chronic Brucella infection.